Triglyceride-glucose-based indices in relation to vitamin D concentrations among adults with metabolic syndrome - Raju Rana; Purnima Adhikari; Ullas Kamath; B. Ananthakrishna Shastri; Shashikiran Umakanth; G. Arun Maiya; Raghavendra Rao S; Vani Lakshmi R; Shobha U. Kamath (PLoS ONE, 2026)
Background The concurrent global epidemics of 25-hydroxyvitamin D (25[OH]D) deficiency and metabolic syndrome (MetS) pose substantial public health challenges. This study investigated the association of the triglyceride-glucose (TyG) related indices with serum 25(OH)D concentration in MetS patients. Methods In this study, we have recruited 1,297 participants (869 men, 428 women) with MetS who underwent regular health checkups between 2021 and 2023. Participants’ demographic, laboratory, and clinical parameters were retrieved, and data were divided into three groups based on the TyG index. Parameters were compared across the TyG index tertiles. Correlation analysis was used to find the association of the TyG index and related indices with 25(OH)D. Results The TyG-body mass index (TyG-BMI) demonstrated a statistically significant but weak negative correlation with serum 25(OH)D levels (r = −0.09, P < 0.001), whereas no significant association was observed between the standard TyG index and 25(OH)D (r = 0.007; P = 0.81). Comparative analysis among tertiles revealed significant differences in lipid profiles and glucose parameters (P < 0.001). Males demonstrated significantly higher TyG index values (P < 0.001), while females showed significantly elevated TyG-BMI (P < 0.001). Serum 25(OH)D concentrations were significantly higher in males compared to females (19.2[8.87] vs 16.6[9.50] ng/mL, P < 0.001). Only 92 (7%) of our study population had a normal level of 25(OH)D (≥30 ng/mL). Conclusion The association between TyG-BMI and vitamin D is weak and of limited clinical relevance. Further prospective studies should be conducted to evaluate the association of these indices with 25(OH)D.